Endocrine risk factors for COVID-19 in context of aging - Máčová, L; Bičíková, M; Hampl, R (Physiological research, 2021)
Aged people are the most susceptible group to COVID-19 infection. Immunosenescence characterized by impairment of immune function with inflamm-aging contributes to pathophysiological alterations, among which endocrine and metabolic diseases are not exception. Diabetes, obesity along with impairment of disorders of thyroid functions are the most frequent ones, the common feature of which is failure of immune system including autoimmune processes. In the minireview we discussed how COVID-19 and aging impact innate and adaptive immunity, diabetes and selected neuroendocrine processes. Mentioned is also beneficial effect of vitamin D for attenuation of these diseases and related epigenetic issues. Particular attention is devoted to the role of ACE2 protein in the light of its intimate link with renin-angiotensin regulating system.
Keywords: přirozená imunita; Host-Pathogen Interactions; Aging; Age Factors; SARS-CoV-2; Immunity, Innate; Endocrine System; endokrinní systém; Animals; lidé; renin-angiotensin systém; interakce hostitele a patogenu; Humans; zvířata; adaptivní imunita; Renin-Angiotensin System; věkové faktory; stárnutí; Adaptive Immunity; Immunosenescence; imunosenescence; COVID-19